2023
DOI: 10.3390/cancers15133320
|View full text |Cite
|
Sign up to set email alerts
|

Radioisotope-Guided Excision of Mediastinal Lymph Nodes in Patients with Non-Small Cell Lung Carcinoma: Feasibility and Clinical Impact

Abstract: Background: Intraoperative localisation of nodal disease in non-small cell lung cancer (NSCLC) can be challenging. Lymph node localisation via radiopharmaceuticals is used in many conditions; we tested the feasibility of this approach in NSCLC. Methods: NSCLC patients were prospectively recruited. Intraoperative peri-tumoral injections of [99mTc]Tc-albumin nanocolloids were performed, followed by removing the tumour and locoregional lymph nodes. These were examined ex vivo with a gamma probe and labelled senti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Concerning previous literature, the increase in recent reports on the use of radio-guided tools to support surgery con rms that this is a growing eld. However, the vast majority of work is con ned to oncology and adult patient settings [10][11][12][13]. In our literature review, we found very few studies in which a radioguided tool has been used in pediatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning previous literature, the increase in recent reports on the use of radio-guided tools to support surgery con rms that this is a growing eld. However, the vast majority of work is con ned to oncology and adult patient settings [10][11][12][13]. In our literature review, we found very few studies in which a radioguided tool has been used in pediatric surgery.…”
Section: Discussionmentioning
confidence: 99%